CFD ANALYSIS OF NATURAL CONVECTION IN A CUBIC ENCLOSURE HEATED FROM A SIDE WALL WITH EXPERIMENTAL VERIFICATION USING PIV - Kurekci, Nuri Alpay (AMER SOC MECHANICAL ENGINEERS, 2010)
Natural convection of air in a cubical volume is investigated experimentally and numerically. A cubical volume of 20x20x20 cm dimensions was built for the experimental study. One of the vertical walls covering the volume is hot, the other one is cold and the rest are adiabatic. Three walls are made of aluminum and the others are made of heat-resistant glass. The hot wall temperature is kept constant during the experiments by means of an electrical heater. The cold wall is at the ambient temperature. Other adiabatic surfaces are insulated with polyurethane foam. Experiments are performed in an air-conditioned room at 21 degrees C. PIV (Particle Image Velocimetry) is used for velocity measurements. The FLUENT CFD software package is used for the numerical study. A three-dimensional solution is obtained for the laminar flow case for a 61x61x61 grid. The numerical and experimental results are compared with each other for the validation of the numerical solution under the testing conditions of T-H=69 degrees C, T-C=41 degrees C and Ra=1.3x10(7). Results obtained from the numerical and experimental studies are in a reasonably good agreement with each other.
Keywords: HOLOGRAPHIC-INTERFEROMETRY; RECTANGULAR ENCLOSURES; Engineering